2023
DOI: 10.3390/ijms24087100
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Lesions and Reduced Life Span of Red Blood Cells in Preeclampsia as Evidenced by Atomic Force Microscopy

Abstract: Preeclampsia (PE) presents with maternal de novo hypertension and significant proteinuria and is one of the leading causes of maternal and perinatal morbidity and mortality with unknown etiology. The disease is associated with inflammatory vascular response and severe red blood cell (RBC) morphology changes. This study examined the nanoscopic morphological changes of RBCs from PE women versus normotensive healthy pregnant controls (PCs) and non-pregnant controls (NPCs) applying atomic force microscopy (AFM) im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…As reported in our previous publications and other studies [ 27 , 45 , 46 , 47 , 48 ], the observed changes in cell shape may be associated with damage to local membrane and cytoskeletal connections. The cytoskeleton comprises a network of proteins, predominantly spectrin tetramers, linked with complexes of actin, protein 4.1R, ankyrin, as well as tropomyosin, tropomodulin, adducin, and dematin [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…As reported in our previous publications and other studies [ 27 , 45 , 46 , 47 , 48 ], the observed changes in cell shape may be associated with damage to local membrane and cytoskeletal connections. The cytoskeleton comprises a network of proteins, predominantly spectrin tetramers, linked with complexes of actin, protein 4.1R, ankyrin, as well as tropomyosin, tropomodulin, adducin, and dematin [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 80%
“…The cytoskeleton comprises a network of proteins, predominantly spectrin tetramers, linked with complexes of actin, protein 4.1R, ankyrin, as well as tropomyosin, tropomodulin, adducin, and dematin [ 48 , 49 ]. The integrity and flexibility of the membrane is largely maintained by the interaction of the spectrin-ankyrin band 3 complex [ 47 , 50 ]. In addition, disruption of these bonds can cause spectrin tetramers to dissociate into dimers [ 51 ], and the protein structures of the matrix network can undergo polymerization and aggregation [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive decrease of RBC membrane elasticity or de-formability in some pathological conditions is indicative of abnormal cell morphology and damaged RBC capacity to adequately adapt its shape to navigate blood vessels, resulting in impaired hemorheology [58]. Recently, we have reported impaired membrane integrity and the presence of RBCs with unusual morphology in preeclamptic women [59]. A great percentage of schistocytes (fragmented red blood cells) was also found in peripheral blood smears of the samples from patients with hypertensive disorders of pregnancy [60].…”
Section: Changes In the Rheological Features Of Rbcs In Preeclampsiamentioning
confidence: 99%
“…Oxidative stress was chemically induced using hydrogen peroxide (H1009 Sigma-Aldrich Pty Ltd., an affiliate of Merck KGaA, Darmstadt, Germany) on newly isolated RBCs from three healthy pregnant women who were not included in the control group PC according to the protocol described in [59]. In brief, RBCs were treated for 4 h at 37 • C with 200 mM, 300 mM, and 400 mM H 2 O 2 .…”
Section: Preparation Of Oxidized Rbcsmentioning
confidence: 99%